Fuzzy Inference Systems Tuning with Optimization Algorithms for Solar Flares Classification - Ramos, Liz Angélica; Bustos Pinzón, Alex Francisco; Melgarejo R., Miguel A.; Vargas Domínguez, Santiago (TECCIENCIA, 2017)
In this work we describe the implementation and analysis of different optimization algorithms used for finding the best set of parameters for a Fuzzy Inference System intended to classify solar flares. The parameters will be identified among a universe of possible solutions for the algorithms, and the system will be tested in the particular case of dealing with the aim of classifying the solar flares.